THE EFFICIENCY OF PHYSICAL THERAPY IN A CHILD WITH FACIAL PARESIS - Marinela RAŢĂ (Editura Universitatii Transilvania din Brasov, 2018)
Paralysis is a disorder of the voluntary motor activity that can occur in quantitative terms by reducing the force, amplitude and speed parameters of the movement. The prognosis in facial paralysis is generally good, with 85% of patients experiencing improvement three weeks after the onset of the disease. The present paper aims to demonstrate that early intervention through physical therapy will prevent the sequelae from being installed in a child with facial paresis, and at the same time will facilitate the condition of the subject throughout the therapeutic intervention. For evaluation, we used the House-Brackmann Scale, the Sunnybrook Scale, muscle tone testing, tactile, thermal, and pain sensitivity. The results obtained demonstrate the effectiveness of physical therapy in a child with facial paresis, the applied intervention program succeeding to combat the facial asymmetries, to restore muscle tone and to recover all forms of lost sensitivity.